Medicinal effect and its JP2/RyR2-based mechanism of Smilax glabra flavonoids on angiotensin II-induced hypertrophy model of cardiomyocytes. (1st July 2015) - Cai, Yueqin; Tu, Jue; Pan, Shuizhen; Jiang, Jianping; Shou, Qiyang; Ling, Yun; Chen, Yunxiang; Wang, Dejun; Yang, Weiji; Shan, Letian; Chen, Minli
Abstract: Ethnopharmacological relevance: Rhizome and root of Smilax glabra Roxb ( Liliaceae family) is a widely used traditional Chinese medicine (TCM) named Tu-fu-ling (TFL) for cardiac disease therapy. The TFL flavonoids (TFLF) has been extracted and proven to possess the anti-cardiac hypertrophy effect in our previous reports. Such effect could be mediated by the modulation of intracellular Ca 2+ flux in myocardial cells, in which junctophilin-2 (JP2) and ryanodine receptor 2 (RyR2) play an important role. However, its mechanism of the anti-cardiac hypertrophy effect remains unclarified. Materials and methods: 2 μmol/L Ang II was applied to induce hypertrophy model of rat primary cardiomyocytes. After treatment of TFLF at 0.25, 0.5 and 1.0 mg/ml, the cell size was microscopic measured, and the protein and mRNA expressions of JP2 and RyR2 in cardiomyocytes were estimated by immunofluorescence imaging, ELISA and real-time PCR assay. Results: Obvious hypertrophy of cardiomyocytes was induced by Ang II but reversed by TFLF from 0.5 to 1.0 mg/ml. The protein and mRNA expressions of JP2 and RyR2 in cardiomyocytes were also inhibited by Ang II but restored by TFLF at its dose range. Such effect of TFLF was exerted at a dose dependent manner, which was even better than that of verapamil. Conclusions: Our findings may evidence the correlation between JP2/RyR2 and myocardiac hypertrophy, and indicate the JP2/RyR2-mediated anti-hypertrophy mechanism of TFLF for the first time. It deserves to be developed as a promising TCM candidate of new drug for myocardial hypertrophy treatment. Graphical abstract: